INDIKATOR YANG MEMPENGARUHI DINAMIKA CADANGAN DEVISA DI INDONESIA SEBELUM DAN SESUDAH ADANYA KRISIS GLOBAL - Mita Pratiwi; Rifki Khoirudin (Fakultas Ekonomi Universitas Islam Al-Azhar, 2022)
This research aims to analyze the influence of exports, imports, exchange rates, inflation, foreign debt on Indonesia's foreign exchange reserves. This study uses time series data in 2000-2020 (monthly) obtained from Bank Indonesia and the Central Statistics Agency. In this study researchers used multiple linear regression methods with the help of E-Views9 software. The results showed partial exports, exchange rates, inflation and foreign debt had a significant effect on foreign exchange reserves. Based on the results obtained, it can be explained that exports have a significant positive effect on foreign exchange reserves, exchange rates have a significant negative effect on foreign exchange reserves, inflation has a significant negative effect on foreign exchange reserves, and foreign debt has a significant positive effect on foreign exchange reserves. As for import variables, negatively insignificant influence on foreign exchange reserves. In addition, simultaneously the overall variable affects 98.5071% of foreign exchange reserves, while the rest is influenced by other variables outside of the variables used.